Outcome of a screening programme for the prevention of neonatal invasive early-onset group B Streptococcus infection in a UK maternity unit: an observational study. Issue 4 (18th April 2017) - Gopal Rao, G; Nartey, G; McAree, T; O'Reilly, A; Hiles, S; Lee, T; Wallace, S; Batura, R; Khanna, P; Abbas, H; Tilsed, C; Nicholl, R; et al.
Abstract : Background: Against a background of failure to prevent neonatal invasive early-onset group B Streptococcus infections (GBS) in our maternity unit using risk-based approach for intrapartum antibiotic prophylaxis, we introduced an antenatal GBS carriage screening programme to identify additional women to target for prophylaxis. Objectives: To describe the implementation and outcome of an antepartum screening programme for prevention of invasive early-onset GBS infection in a UK maternity unit. Design: Observational study of outcome of screening programme (intervention) with comparison to historical controls (preintervention). Setting: Hospital and community-based maternity services provided by Northwick Park and Central Middlesex Hospitals in North West London. Participants: Women who gave birth between March 2014 and December 2015 at Northwick Park Hospital. Methods: Women were screened for GBS at 35–37 weeks and carriers offered intrapartum antibiotic prophylaxis. Screening programme was first introduced in hospital (March 2014) and then in community (August 2014). Compliance was audited by review of randomly selected case records. Invasive early-onset GBS infections were defined through GBS being cultured from neonatal blood, cerebrospinal fluid or sterile fluids within 0–6 days of birth. Main outcome: Incidence of early-onset GBS infections. Results: 6309 (69%) of the 9098 eligible women were tested. Screening rate improved progressively from 42% in 2014 to 75% in 2015. Audit showed that 98% of women accepted the offer of screening. Recto-vaginal GBS carriage rate was 29.4% (1822/6193). All strains were susceptible to penicillin but 11.3% (206/1822) were resistant to clindamycin. Early onset GBS rate fell from 0.99/1000 live births (25/25276) in the prescreening period to 0.33/1000 in the screening period (Rate Ratio=0.33; p=0.08). In the subset of mothers actually screened, the rate was 0.16/1000 live births (1/6309), (Rate Ratio=0.16; p<0.05). Conclusions: Our findings confirm that an antenatal screening programme for prevention of early-onset GBS infection can be implemented in a UK maternity setting and is associated with a fall in infection rates.